Humor Analysis Of Ideological Discussion In Twitter Account Interactions @NUgarislucu and @MuhammadiyinGL - Ahmad Efendi (ITScience (Information Technology and Science), 2021)
This study aims to analyze the humorous interaction of ideological discourses between twitter account @NUgarislucu and @MuhammadiyinGL. In social media twitter because they often interact with organizational ideological issues in a joke. Researchers cite 5 direct and indirect interactions between the @NUgarislucu and @MuhammadiyinGL twitter accounts during January-February 2021 with different interaction backgrounds. In the interaction between the two accounts above, there are actually ideologies of their respective organizations that want to be conveyed to the public. However, the two accounts also show the general public that conveying beliefs, religious doctrines can actually be done with jokes and humor. You don't have to think that one group is right and the other is wrong.